2021
DOI: 10.1016/j.sjbs.2021.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different cooking methods on loss of iron and zinc micronutrients in fortified and non-fortified rice

Abstract: Malnutrition is considered as major public health concern and is emerging challenge to food and nutrition security particularly in developing countries. Rice is the staple food and consumed by the half of the world's population which is the source of daily requirement of the nutrients. Attempts are being made to fortify rice with micronutrients, but the loss or retention of these micronutrients in different cooking methods is not well studied and documented especially in fortified rice. In the present study, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Various sample pre-treatment methods are used when determining fruit Zn concentrations, including peeling, coring, sectioning, cleaning, drying, and digestion [19,20]. In our study, the digestion solution easily overflowed during the digestion of fresh and freezedried pear samples, and a long pre-digestion period at low temperatures was required.…”
Section: Choice Of Methods For Sample Preparationmentioning
confidence: 91%
“…Various sample pre-treatment methods are used when determining fruit Zn concentrations, including peeling, coring, sectioning, cleaning, drying, and digestion [19,20]. In our study, the digestion solution easily overflowed during the digestion of fresh and freezedried pear samples, and a long pre-digestion period at low temperatures was required.…”
Section: Choice Of Methods For Sample Preparationmentioning
confidence: 91%
“…136 With proper cooking methods, cooked foods will retain more micronutrients, thus helping to combat malnutrition and improve health. 137 Another popular carrier is dairy products. Compared to standard non-fortified milk, consumption of zinc-fortified drinking skim milk (Zn-Fmilk) increases very old cell-mediated immunity represented by thymosin activity and release of some cytokines (interleukin-12p70 and interferon-γ).…”
Section: Applications In Fortified Foodsmentioning
confidence: 99%
“…Furthermore, fortified rice has a high stability of micronutrients during storage, even at high temperatures and humidity, over a longer period of time 136 . With proper cooking methods, cooked foods will retain more micronutrients, thus helping to combat malnutrition and improve health 137 …”
Section: Application Of Zinc Supplementsmentioning
confidence: 99%
“…As of year 2022, seven countries have mandatory legislation for rice fortification, that is, Solomon Islands, Costa Rica, Nicaragua, Panama, Papua New Guinea, the Philippines, and the USA. Along with these, more than 86 countries are working and scaling fortification in cereals grain. High retention during cooking: Mohibbe et al (2021) reported that fortified polished rice had higher micronutrient contents (106.31 ± 12.56 mg iron and 97.72 ± 9.75 mg zinc) than non-fortified polished rice (7.44 ± 1.05 iron, 14.74 ± 2.94 mg zinc). During cooking, fortified rice suffered more percentage loss of micronutrients, as compared with non-fortified rice.…”
Section: White Rice (Oryza Sativa) As a Suitable Tool For Fortificati...mentioning
confidence: 99%
“…6. High retention during cooking: Mohibbe et al (2021) reported that fortified polished rice had higher micronutrient contents (106.31 ± 12.56 mg iron and 97.72 ± 9.75 mg zinc) than non-fortified polished rice (7.44 ± 1.05 iron, 14.74 ± 2.94 mg zinc). During cooking, fortified rice suffered more percentage loss of micronutrients, as compared with non-fortified rice.…”
Section: High Prevalence Of Anaemiamentioning
confidence: 99%